Kajian Teoretis tentang Dampak Kebijakan Moneter terhadap Tingkat Inflasi di Negara Berkembang - Berkat Jaya Zalukhu; Fajarman Lahagu; Jefrin Zalukhu; Rifqah Harahap (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This article presents a theoretical review of the relationship between monetary policy and inflation rates in developing countries. High inflation remains a major challenge for developing economies due to global price fluctuations, import dependency, and weak domestic economic structures. Monetary policy instruments such as policy interest rates, open market operations, and reserve requirements play a vital role in controlling inflation, although their effectiveness is often hampered by shallow financial markets, low financial inclusion, and limited central bank credibility. Moreover, external factors such as imported inflation reduce the ability of monetary policy to maintain price stability. This study highlights the importance of digital innovation, including the use of big data, digital payment systems, and real-time analytics to enhance monetary policy effectiveness. It concludes that structural reforms, stronger central bank credibility, and strategic adoption of digital innovation are essential to achieve price stability and sustainable economic growth in the globalization era.